Learning designs for work and power materials using didactical situation analysis approach - Dwi Ajni Shafarwati; Asep Herry Hermawan; Laksmi Dewi (Himpunan Pengembang Kurikulum Indonesia, 2025)
Junior high school students often find learning obstacles in thinking critically and systematically in solving problems in natural science subjects, particularly for work and power materials. This is caused by the sequence and/or stages of curriculum presentation. Efforts to improve the sequence and/or stages of curriculum presentation have been made by examining various alternatives in accordance with students' previous learning experiences as well as their capacity and potential through didactical situation analysis. This study aims to improve students' ability to think critically and systematically in finding solutions to problems given through learning design and developing teachers' pedagogical skills. This qualitative study used a didactical design research design. Data were collected by interviewing students and teachers regarding the delivery of work and power materials. Besides, data collection also involved a documentation study of the modules and teaching materials, including the textbooks. Data were analyzed using an interactive model covering 1) data reduction; 2) data presentation; and 3) Conclusion. The result of the study was in the form of learning designs that consider learning obstacles by predicting students' answers and teacher anticipation before, during, and after learning. Students were also given sharing tasks for the application of the material in daily life. Abstrak Kesulitan belajar yang sering dialami peserta didik sekolah menengah pertama pada mata pelajaran IPA materi daya dan usaha adalah kemampuan berpikir secara kritis dan sistematis dalam mengatasi masalah yang diberikan. Munculnya masalah tersebut kemungkinan disebabkan oleh urutan dan atau tahapan sajian kurikulum. Upaya yang dilakukan untuk memperbaiki urutan dan atau tahapan sajian kurikulum, dengan mengkaji berbagai alternatif yang sesuai pengalaman belajar peserta didik sebelumnya, serta kapasitas dan potensinya melalui analisis situasi didaktis. Penelitian bertujuan meningkatkan kemampuan peserta didik berpikir kritis dan sistematis dalam menemukan solusi terhadap masalah yang diberikan melalui desain pembelajaran serta mengembangkan kemampuan pedagogik guru. Penelitian menggunakan metode kualitatif dengan desain Didactical Design Research. Pengumpulan data dilakukan dengan wawancara terhadap peserta didik dan guru terkait cara penyampaian materi daya dan usaha. Teknik lainnya adalah studi dokumentasi terhadap modul dan bahan ajar yang digunakan serta pengkajian berbagai textbook. Teknik analisis data yang digunakan adalah analisis data model interaktif yang mencakup 1) Reduksi data; 2) Penyajian secara naratif; dam 3) Penarikan kesimpulan. Hasil yang diperoleh berupa desain pembelajaran yang memperhatikan hambatan belajar dengan memprediksikan jawaban peserta didik dan antisipasi guru pada sebelum, saat dan setelah pembelajaran. Selain itu peserta didik diberikan sharing task yang merupakan aplikasi materi dalam kehidupan sehari-hari. Keywords: daya; desain pembelajaran; situasi didaktis; usaha